Nepal : 2000 Economic Update - World Bank (Washington, DC, 2013)
The report is one of the documents in support of discussions for an upcoming Nepal Development Forum meeting, and, updates the macroeconomic development, and performance of related key areas of the economy, specifically, the period following the last economic update of November 1997, focusing on the provision of an overall framework for the reform agenda. The study reviews the economic growth of the country, which, despite certain growth, enabled by a series of reforms in the late eighties, has slowed down in recent years, largely due to political instability. Consequently, economic performance has been unsatisfactory, with almost no progress in reducing poverty, nor in addressing structural reforms. Forceful actions to accelerate economic development are recommended, namely, to improve public resource management, by changing the role of the public sector, towards the improvement of public expenditures, and revenue reforms. Furthermore, it is necessary to provide a level playing field for the private sector vis-e-vis public enterprises, enhancing competitiveness, and, most importantly, to establish the rule of law, in support of private sector activities. Conclusions address critical issues, such as financial sector reforms, institutional capacity building, decentralization, and the promotion of ownership, and participation.